Lung toxicity after radiation in childhood: Results of the International Project on Prospective Analysis of Radiotoxicity in Childhood and Adolescence. Issue 2 (November 2017) - Stoppel, Gerhild; Eich, Hans-Theodor; Matuschek, Christiane; Kortmann, Rolf-Dieter; Meyer, Frank; Martinsson, Ulla; Nilsson, Kristina; Kristensen, Ingrid; Vordermark, Dirk; Willich, Normann; Christiansen, Hans; Koch, Raphael; et al.
Abstract: Background and purpose: This study presents the evaluation of acute and late toxicities of the lung in children and adolescents after irradiation in terms of dose–volume effects. Materials and methods: Irradiated children and adolescents in Germany have prospectively been documented since 2001 in the "Registry for the Evaluation of Side-Effects after Radiotherapy in Childhood and Adolescence (RiSK)"; in Sweden since 2008 in the RADTOX registry. Results: Up to April 2012, 1, 392 children were recruited from RiSK, and up to June 2013, 485 from the RADTOX-registry. Of these patients, 295 were irradiated to the lung. Information about acute toxicity was available for 228 patients. 179 patients have been documented concerning late toxicity (≥grade 1: n = 28). The acute toxicity rate was noticeably higher in children irradiated with 5–20 Gy ( p < 0.05). In the univariate analysis, a shorter time until late toxicity was noticeably associated with irradiation with 5–15 Gy (p < 0.05). Conclusion: Acute and late toxicities appear to be correlated with higher irradiation volumes and low doses. Our data indicate that similar to the situation in adult patients, V5, V10, V15 and V20 should be kept as low as possible (e.g., at least V5 < 50%, V10 and V15 < 35% and V20 < 30%) in children and adolescents to lower the risk of toxicity.